Comparing User Experience Poro and Obenkyou Applications Using the User Experience Questionnaire - Mia Putri Yeza; Fauzi Adi Saputra; Marsya Halya Alfrida; Capriandika Putra Susanto; Anka Luffi Ramdani; Humannisa Rubina Lestari (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The success of educational apps is closely tied to the quality of user experience (UX). This study compared the UX of two Japanese language learning apps, Poro and Obenkyou, to examine the impact of different instructional designs. Sixty-five respondents, all of whom had used both apps for at least one week, rated six UX dimensions-Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty-using the User Experience Questionnaire (UEQ). Data analysis using the official UEQ tool and independent t-tests showed that both apps received positive ratings on all dimensions, but Poro consistently achieved higher mean scores (e.g., Attractiveness: 1.83 vs. 1.18; Stimulation: 1.89 vs. 1.13). These results indicate a significant difference in user perceptions, with gamification contributing to better UX. This study highlights the importance of design strategies in educational apps.